Soluble guanylate cyclase stimulator riociguat and phosphodiesterase 5 inhibitor sildenafil ameliorate pulmonary hypertension due to left heart disease in mice. (1st August 2016) - Pradhan, Kabita; Sydykov, Akylbek; Tian, Xia; Mamazhakypov, Argen; Neupane, Balram; Luitel, Himal; Weissmann, Norbert; Seeger, Werner; Grimminger, Friedrich; Kretschmer, Axel; Stasch, Johannes-Peter; Ghofrani, Hossein Ardeschir; et al.
Abstract: Background: Presence of pulmonary hypertension (PH) and right ventricular dysfunction worsens prognosis in patients with chronic heart failure (CHF). Preclinical and clinical studies suggest a role for the impaired nitric oxide (NO)-soluble guanylate cyclase (sGC)-cyclic guanosine monophosphate (cGMP) signaling pathway in both PH and CHF. Hence, we examined the effects of the NO–sGC–cGMP pathway modulation by the PDE5 inhibitor sildenafil or sGC stimulator riociguat on pulmonary hemodynamics and heart function in a murine model of secondary PH induced by transverse aortic constriction. Methods: C57Bl/6N mice were subjected to transverse aortic constriction (TAC) for 6 weeks to induce left heart failure and secondary PH and were subsequently treated with either sildenafil (100 mg/kg/day) or riociguat (10 mg/kg/day) or placebo for 2 weeks. Results: Six weeks after surgery, TAC induced significant left ventricular hypertrophy and dysfunction associated with development of PH. Treatment with riociguat and sildenafil neither reduced left ventricular hypertrophy nor improved its function. However, both sildenafil and riociguat ameliorated PH, reduced pulmonary vascular remodeling and improved right ventricular function. Conclusions: Thus, modulation of the NO–sGC–cGMP pathway by the PDE5 inhibitor sildenafil or sGC stimulator riociguat exerts direct beneficial effects on pulmonary hemodynamics and right ventricular function in the experimental model of secondary PH due to left heart disease and these drugs may offer a new therapeutic option for therapy of this condition.